MICROBIOLOGICAL ASSESSMENT OF SHARRI CHEESE PRODUCED UNDER TRADITIONAL AND INDUSTRIAL CONDITIONS - Ferati, Ismail; Bijo, Bizena; Idrizi, Xhezair; Durmish, Namik; Xhabiri, Gafur (European Scientific Journal, ESJ, 2013)
Sharri cheese is produced from sheep milk. The production of this cheese is an early tradition in the region of Sharri. The traditional from is produced from unpasteurized milk. Recently, this type of cheese is produced in industrial conditions. The purpose of this paper is to evaluate and compare the microbiological situation of Sharri cheese, produced in traditional and in industrial conditions. Throughout this study, we have investigated the effect of some physical and chemical parameters upon on Staphylococcus coagulase positive and aerob mesophilic bacteria. in Sharri cheese. Considering that Staphylococcus coagulase positive is able to produce enterotoxines, samples have been analysed for the presence of toxins – VIDAS.